Business Performance Boosted: The Role of Entrepreneurial Characteristics and Startup Strategies in Bangka Belitung Islands Province - Maya Yusnita; Dian Prihardini Wibawa; Reniati Reniati; Hamsani Hamsani; Dini Oktariani; Padlun Fauzi; Indah Noviyanti (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2023)
This study aims to analyze the influence of entrepreneurial characteristics and startup strategies in improving business performance in Bangka Belitung Islands Province. Data collection in this study was conducted by survey method with in-depth interviews and questionnaires, providing a list of questions and statements to the 100 respondents, in this case, Startup Business in the Bangka Belitung Islands Province. The data analysis technique used the SEM Moderating approach with SmartPLS (Partial Least Square). The results indicate that Entrepreneurial characteristics positively influence improving business performance in the Bangka Belitung Islands Province. The startup strategy has a positive effect on improving business performance in the Bangka Belitung Islands Province. Entrepreneurial characteristics and startup strategy together strongly influence business performance in the Bangka Belitung Islands Province.